Peran pemerintah daerah dalam mendukung potensi indikiasi geografis produk pertanian - Ranitya Ganindha; Sukarmi Sukarmi (University of Merdeka Malang, 2020)
The recording of Geographical Indications itself has benefits that can increase the economic benefits of the product. Registration of Geographical Indication Certification can increase the potential of a product of biological wealth. The advantage that is obtained if a product is protected by Geographical Indications is that the product will be superior and have higher competitiveness compared to similar products. The local government of Malang Regency and local farming communities in Malang Regency have awareness regarding the protection of Geographical Indications. One of the programs launched by the government through the Ministry of Law and Human Rights is the Increase in the Number of Geographical Indications. Registration of Geographical Indications not only gives an economic increase, but also has a long impact on the progress of the tourism sector as one of the superior programs that the Malang Regency Government wants to achieve. This research is a juridical empirical research with a qualitative interpretation. Research using the empirical method means that the research is carried out directly in the field to identify problems and find solutions to problems that occur. The outputs produced through this research are studies, draft regional regulations, and journals that can be used as reference material for the Malang Regency Government.How to cite item: Ganindha, R., Sukarmi, S. (2020). Peran pemerintah daerah dalam mendukung potensi indikiasi geografis produk pertanian. Jurnal Cakrawala Hukum, 11(2), 211-221. doi:https://doi.org/10.26905/idjch.v11i2.3970